Leadership Caderization Development at Pesantren Darunnajah Jakarta - Fajar Suryono; Mohd Rumaizuddin Bin Ghazali; Muhammad Bin Hashim (East Asian Journal of Multidisciplinary Research, 2023)
This research was motivated by the writer's anxiety about the weaknesses of pesantren institutions in educating successive leaders because pesantren rarely survived more than a century. As a form of effort toward realizing ideal leadership capacity development, the writer chose Pesantren Darunnajah Jakarta as a subject of research. This type of research is qualitative according to the Case Study Research Theory. Based on the results, the researcher found that the concept of leadership cadre is delegation, transformation based on the values of Islamic teachings that involve all pesantren staff in the educational process from the pesantren leadership, and implementation of leadership cadre development at the pesantren Darunnajah Jakarta, which is contained in the guidance and coaching system, namely the Total Quality Management system, for 24 hours so that prospective cadres of leaders always receive supervision, guidance, and coaching.